Understanding Religion from a Cultural Perspective: The Role of the Anthropological Approach in Islamic Studies Methodology - S. Nor Hasanah (International Journal on Advanced Science, Education, and Religion, 2026)
Religion and culture are closely interconnected aspects of human society. In Islam, religious teachings originate from the Qur'an and Sunnah as normative foundations, while religious practices develop within diverse socio-cultural contexts. Therefore, anthropology has become an important approach in Islamic Studies because it enables scholars to understand how Islamic teachings are interpreted, practiced, and transformed within different cultural settings. This article aims to examine the role of anthropological approaches in understanding religion from a cultural perspective and their contribution to contemporary Islamic Studies. This study employs a qualitative library research method by analyzing the Qur'an, Hadith, classical and contemporary tafsir, anthropological literature, and recent scholarly publications. Data were analyzed using content analysis. The findings indicate that anthropological approaches provide significant contributions to explaining the interaction between religious texts and social realities. Anthropology enriches Islamic Studies by offering contextual, empirical, and culturally sensitive perspectives without neglecting the normative foundations of Islam. Furthermore, this approach supports the development of moderate, inclusive, and adaptive Islamic scholarship in responding to contemporary social and technological changes.